Salicylaldehyde thiazolyl hydrazones as ligands - Yilmaz, I; Çukurovali, A (Wiley, 2003)
Novel bidentate Schiff base ligands, 2(2-hydroxy N-5-chloro/nitro)benzaldehyde-[4-(3-methyl-3-mesitylcyclobutyl)-1,3-thiazol-2-yl]hydrazone, and their metal complexes have been prepared and characterized by elemental analyses, IR, C-13 and H-1 NMR spectra, and magnetic susceptibility measurements. All the complexes were found to be mononuclear. (C) 2003 Wiley Periodicals, Inc.
Keywords: Gossypol; Complexes; Potent; Acid